Patterns of Use and Predictors of Receipt of Antibiotics in Women Undergoing Cesarean Delivery. Issue 2 (June 2015) - Brubaker, S.G.; Friedman, A.M.; Cleary, K.L.; Prendergast, E.; D'Alton, M.E.; Ananth, C.V.; Wright, J.D.
<x xml:space="preserve">Abstract</x> (Obstet Gynecol. 2014;124(2 pt 1):338–344)